Polyethersulfone 3-Aminopropyltriethoxysilane-Silica Composite Hollow Fiber Membrane For Synthetic Oil-In-Water Emulsion Separation - Otitoju, Tunmise Ayode (2019)
Membrane fouling effect by oil is a critical issue in wastewater applications. Fouling can be mitigated by functionalizing the membrane with enhanced hydrophilic properties. Although, previous research have concluded that an increase in surface hydrophilicity is a feasible mechanism for fouling mitigation, other parameters such as membrane roughness and morphology may contribute as well. In this work, 3-aminopropyltriethoxysilane modified silica (APTES-SiO2) particle was synthesized via one pot reaction modification. Response surface methodology based on central composite design was used to prepare the PES composite HF membranes via dry-wet spinning process. The result shows that the ratio of polyethylene glycol to APTES-SiO2 particles must be equal to 1 or more than unity to ensure better dispersion of APTES-SiO2 in the PES matrix as well as improved performance. The optimum dope formulation obtained was subsequently used to develop PES/APTES-SiO2 composite membrane by varying ethanol fraction the bore fluid composition. In terms of bore fluid composition, HF membrane spun with 25/75 wt.% of ethanol shows a better surface morphology and improved permeation properties. Membrane properties were studied in terms of pore size, porosity, roughness, hydrophilicity, mechanical and thermal properties. The SEM images of the HF membranes shows that the particles have been successfully incorporated in the membrane matrix and well dispersed. The surface roughness of all composite membranes were lower as compared to the controlled membrane. The PES/APTES-SiO2 composite membrane show an improved hydrophilicity, permeability and anti-fouling effects when tested for wastewater applications. The rejection performance of PES/APTES-SiO2 composite membrane during filtration of synthetic oil in water shows that the incorporation of 2.5 wt.% of APTES-SiO2 was able to remove 99.87 of oil as compared to only 97.23 for pristine membrane. It was found that the composite membranes had low relative flux reduction, superior flux recovery ratio and fouling resistance as compared to the controlled which can be as a result of the decrease in surface roughness, pore structure and well dispersed APTES-SiO2 particles on the membrane surface. To get more details on the performance of the composite membrane, different operating conditions such as transmembrane pressure, feed concentration, and feed flow rates were also investigated. The intermediate block model was identified as the most critical factor that contributed to membrane fouling. This work demonstrated that by functionalizing SiO2 surface with APTES, HF membranes with low surface roughness and anti-fouling properties can be achieved for effective removal of oil from synthetic oil-in-water emulsion.